The Limitation of The Effectiveness of Google Classroom as An Online Platform in During the Coved-19 Pandemic in Iraqi Universities - Jawoosh, Hayder N.; Alshukri, Harith Abdelelah; Jawoosh, Fatmah Nazar; Azzawi, Zahraa Saad; Kzar, Mazin Hadi (International Journal of Membrane Science and Technology, 2023)
The popularity of the Web and rapid developments in its tools have had a clear impact on the educational field. Many countries try to take benefit of the advantages provided by the Web like online learning programs. This paper shows the effectiveness of the Google Classroom platform as an alternative to material lectures on the campus during the application of quarantine considering the outbreak of the Coronavirus (COVID-19). This study was applied to the Iraqi public and private universities scattered in different regions of the country. The data was collected by sending an online questionnaire. Technology Acceptance Model (TAM) was adapted to examine the effectiveness of learning online activity. The number of answers was 1704, which were collected online from male and female college students. The student's difficulty in dealing with Google Classroom as an alternative to attending inside campus appears in the data analysis section, where the data of the statistical analysis of this study showed negative results in terms of Google Classroom subscales like the ease of use, perceived usefulness, communication, and interaction and perceive instruction delivery. On the other hand, some positive results appeared related to the student’s satisfaction in using Google Classroom. This finding indicates that Google classroom to be a difficult medium of use for students due to the universities and the lecturers in Iraq never uses such online programs in their studies.